Composite Bonding to Stainless Steel Crowns Using a New Universal Bonding and Single-Bottle Systems - Mohammad Ali Hattan; Sharat Chandra Pani; Mohammad AlOmari (Hindawi Limited, 2013)
Aim. The aim of this study is to evaluate the shear bond strength of nanocomposite to stainless steel crowns using a new universal bonding system. Material and Methods. Eighty (80) stainless steel crowns (SSCs) were divided into four groups (20 each). Packable nanocomposite was bonded to the lingual surface of the crowns in the following methods: Group A without adhesive (control group), Group B using a new universal adhesive system (Scotchbond Universal Adhesive, 3M ESPE, Seefeld, Germany), and Group C and Group D using two different brands of single-bottle adhesive systems. Shear bond strengths were calculated and the types of failure also were recorded. Results. The shear strength of Group B was significantly greater than that of other groups. No significant differences were found between the shear bond strengths of Groups C and D. The control group had significantly lower shear bond strength () to composite than the groups that utilized bonding agents. Conclusion. Composites bonding to stainless steel crowns using the new universal bonding agent (Scotchbond Universal Adhesive, 3M ESPE, Seefeld, Germany) show significantly greater shear bond strengths and fewer adhesive failures when compared to traditional single-bottle systems.